Pyridine derivative-induced fluorescence in multifunctional modified carbon dots and their application in thermometers. Issue 21 (15th May 2017) - Han, Mumei; Wang, Liping; Bai, Liang; Zhou, Yunjie; Sun, Yue; Li, Hao; Huang, Hui; Liu, Yang; Kang, Zhenhui
Abstract : NS-Cdots can be used as fluorescent probes for cell imaging and as effective thermometers. Abstract : We present a simple hydrothermal method to fabricate multifunctional modified carbon dots (with –COOH, –OH, –SH, and –NH2 groups, named NS-Cdots) using citric acid andl -cysteine as raw materials. The functional NS-Cdots exhibit high fluorescent quantum yield (38.9%), low cytotoxicity and good biocompatibility. A reasonable photoluminescence mechanism of the NS-Cdots was proposed in which the pyridine derivatives serve as conjugating units and dominate the main emission behavior. The NS-Cdots can also be used as excellent fluorescent probes for cell imaging in vitro and as effective thermometers with a wide temperature detection range from 20 °C to 95 °C.